The broader phenotypic spectrum of congenital caudal abnormalities associated with mutations in the caudal type homeobox 2 gene. Issue 2 (28th October 2021) - Stevens, Servi J. C.; Stumpel, Constance T. R. M.; Diderich, Karin E. M.; van Slegtenhorst, Marjon A.; Abbott, Mary‐Alice; Manning, Courtney; Balciuniene, Jorune; Pyle, Louise C.; Leonard, Jacqueline; Murrell, Jill R.; van de Putte, Romy; van Rooij, Iris A. L. M.; et al.
Abstract: The caudal type homeobox 2 ( CDX2 ) gene encodes a developmental regulator involved in caudal body patterning. Only three pathogenic variants in human CDX2 have been described, in patients with persistent cloaca, sirenomelia and/or renal and anogenital malformations. We identified five patients with de novo or inherited pathogenic variants in CDX2 with clinical phenotypes that partially overlap with previous cases, that is, imperforate anus and renal, urogenital and limb abnormalities. However, additional clinical features were seen including vertebral agenesis and we describe considerable phenotypic variability, even in unrelated patients with the same recurrent p.(Arg237His) variant. We propose CDX2 variants as rare genetic cause for a multiple congenital anomaly syndrome that can include features of caudal regression syndrome and VACTERL. A causative role is further substantiated by the relationship between CDX2 and other proteins encoded by genes that were previously linked to caudal abnormalities in humans, for example, TBXT (sacral agenesis and other vertebral segmentation defects) and CDX1 (anorectal malformations). Our findings confirm the essential role of CDX2 in caudal morphogenesis and formation of cloacal derivatives in humans, which to date has only been well characterized in animals. Abstract :